A history of fascia. Issue 7 (1st April 2019) - Adstrum, Sue; Nicholson, Helen
Abstract : Fascia is a generic anatomical term that refers to a variety of the body's soft fibrous connective tissue parts. An expanding interdisciplinary interest in fascia might be accompanied by changes in how fascia is cognized. This study surveys the anatomical portrayal of fascia through history, with the aim of helping contextualize the ways it is now known. A historiographic review of fascia‐related literature written in the English language was undertaken. The anatomical meaning associated with fascia has varied during the 400 years that this term has been incorporated in English‐language medical literature. Fascia has been diversely portrayed as a range of macroscopically discernable body parts, the tissues they are composed of, and a pervasive soft connective tissue network structure. Over the last four centuries, fascia has been described in many ways. Anatomical understanding of fascia has developed over the years and is likely to continue to change with evolving research technologies. Multidisciplinary advances in fascial knowledge could conceivably contribute to improving individual and societal health care. Clin. Anat. 32:862–870, 2019. © 2019 Wiley Periodicals, Inc.